Urbanization and Economic Development in Russia - Evgeniya Kolomak (European Regional Science Association (ERSA), 2012)
The paper studies trends in the urbanization in Russia and compares them with the global ones. Russia has high level of urbanization, urban population reached 73% in 1990, and the rate of urbanization fluctuates around this level past 20 years. The change of the urban population in Russia is influenced by three factors: natality, migration and the administrative reforms. The latter includes the establishing of new urban settlements and transformation of rural settlements into urban or vice versa. Starting in 1992, the low birth rate has become a major factor in reducing the number of urban residents. Immigration from cities was observed in 1991-1992 and it exacerbated the decline of the urban population of Russia. The administrative reorganizations had significant impact on the official statistical data on the urban population in Russia, especially in 1991, 1992, 1999, and 2004. The paper discusses advantages and disadvantages of the urbanization to the economic development and provides empirical analysis of the relationship between the economic growth and the urbanization in Russian regions. Russian regions differ significantly in urbanization, both at the macroeconomic level and the subnational one. Tested hypotheses are the following: 1) urbanization stimulates growth of regional productivity in Russia; 2) the positive effect of urbanization on the regional productivity in Russia is decreasing and at some level becomes an impeding factor; 3) large cities demonstrate higher performance and create positive externalities for the overall regional development. The idea of econometric estimates is to expand an aggregate regional production function including urbanization level and agglomeration capacity of the cities. We use panel annual data for 79 Russian regions and covered period is 2000 – 2008. Estimation tool is fixed effects least squares. The estimates show that increase of share of urban population in the country by 1% gives rise of the average regional productivity by 8%. However, the effect of urbanization is reducing. The growth of a city size per 1 thousand residents would increase economic productivity by 0.1% only. The conclusion is that despite the high level of urbanization in Russia and a number of negative effects of the concentration of economic activity in the cities, the resources of urbanization are not exhausted. Cities develop effectively creating positive externalities and growth impulses on surrounding areas in Russian regions. The potential of changes in the structure of urban settlements in favor of large cities exists, but it is very small.
Keywords: 330